1997
DOI: 10.1074/jbc.272.45.28407
|View full text |Cite
|
Sign up to set email alerts
|

HRX Leukemic Fusion Proteins Form a Heterocomplex with the Leukemia-associated Protein SET and Protein Phosphatase 2A

Abstract: One of the most common chromosomal abnormalities in acute leukemia is a reciprocal translocation involving the HRX gene at chromosome locus 11q23, resulting in HRX fusion proteins. Using the yeast two-hybrid system, in vitro binding studies, and human cell culture coimmunoprecipitation experiments, we show here that a region of the HRX protein that is consistently retained in HRX leukemic fusion proteins interacts directly with SET, another protein implicated in leukemia. We have identified the binding sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 56 publications
(49 reference statements)
3
84
0
Order By: Relevance
“…In addition to its activity as an inhibitor of PP2A, SET is also a potent inhibitor of the tumour suppressor NM23-H1 (Fan et al, 2003). Notably, SET was described as part of a fusion gene with the nucleopore complex protein CAN in a patient with t(6;9)(p23;q34) acute myeloid leukaemia (AML) (Adachi et al, 1994), and it was found associated with the oncoprotein Mll (ALL1, HRX) in leukaemic cell lines (Adler et al, 1997). Thus, it is intuitive that genetic (mutations in the gene encoding a specific PP2A subunits) or functional (e.g.…”
Section: Protein Phosphatase 2a (Pp2a) a Phosphatase With Tumour Supmentioning
confidence: 99%
“…In addition to its activity as an inhibitor of PP2A, SET is also a potent inhibitor of the tumour suppressor NM23-H1 (Fan et al, 2003). Notably, SET was described as part of a fusion gene with the nucleopore complex protein CAN in a patient with t(6;9)(p23;q34) acute myeloid leukaemia (AML) (Adachi et al, 1994), and it was found associated with the oncoprotein Mll (ALL1, HRX) in leukaemic cell lines (Adler et al, 1997). Thus, it is intuitive that genetic (mutations in the gene encoding a specific PP2A subunits) or functional (e.g.…”
Section: Protein Phosphatase 2a (Pp2a) a Phosphatase With Tumour Supmentioning
confidence: 99%
“…These domains do not recognize a specific sequence but rather a structure of cruciform or bent DNA. The MLL AT-hook region was shown to interact with SET protein (not to be confused with SET domain), protein phosphatase 2A (PP2A), and the proapoptotic protein GADD34 [Adler et al, 1997;Adler et al, 1999]. MLL fusion proteins, but not the wild-type MLL, inhibit GADD34-induced apoptosis suggesting that this may be an important factor in MLL-associated leukemias [Adler et al, 1999].…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…It has been identified as a potent inhibitor of protein phosphatase 2A (Li et al, 1996;Adler et al, 1997;Pandey et al, 2003) and as a regulator of DNA replication, chromatin remodeling and gene transcription (Matsumoto et al, 1993;Okuwaki and Nagata, 1998;Shikama et al, 2000;Seo et al, 2001;Cervoni et al, 2002;Kutney et al, 2004).…”
Section: Introductionmentioning
confidence: 99%